In silico analysis and characterization of medicinal mushroom cystathionine beta-synthase as an angiotensin converting enzyme (ACE) inhibitory protein. (February 2022) - Goh, Neng-Yao; Mohamad Razif, Muhammad Fazril; Yap, Yeannie Hui-Yeng; Ng, Chyan Leong; Fung, Shin-Yee
Abstract: Angiotensin-converting enzyme (ACE) regulates blood pressure and has been implicated in several conditions including lung injury, fibrosis and Alzheimer's disease. Medicinal mushroom Ganordema lucidum (Reishi) cystathionine beta-synthase (GlCBS) was previously reported to possess ACE inhibitory activities. However, the inhibitory mechanism of CBS protein remains unreported. Therefore, this study integrates in silico sequencing, structural and functional based-analysis, protein modelling, molecular docking and binding affinity calculation to elucidate the inhibitory mechanism of GlCBS and Lignosus rhinocerus (Tiger milk mushroom) CBS protein (LrCBS) towards ACE. In silico analysis indicates that CBSs from both mushrooms share high similarities in terms of physical properties, structural properties and domain distribution. Protein-protein docking analysis revealed that both GlCBS and LrCBS potentially modulate the C-terminal domain of ACE (C-ACE) activity via regulation of chloride activation and/or prevention of substrate entry. GICBS and LrCBS were also shown to interact with ACE at the same region that presumably inhibits the function of ACE. Graphical Abstract: ga1 Highlights: Lignosus rhinocerus cystathionine-beta synthase (LrCBS) share high sequence similarity with Ganoderma lucidum CBS (GlCBS). In silico analysis indicated that both GlCBS and LrCBS are thermally stable and functionally conserved. LrCBS and GlCBS protein structures were modelled and refined through structural comparisons and stereochemical assessments. LrCBS and GlCBS potentially inhibit catalytic activity of ACE C-terminal domain through prevention of chloride activation.